Factors Affecting the Decision to Choose a Local University in Vietnam - Thuy, Le Thi Thanh (International Journal of Educational Studies, 2020)
Most universities in Vietnam, especially the local ones, are struggling to implement the annual enrollment plan because their enrollment plans have not completed recently. What are the important factors affecting admissions results for local universities? On the basis of the theoretical model, the research has proposed, designed and tested the scale of factors affecting the decision to choose a local university in Vietnam. Through a survey of 412 students at local universities, the regression model showed that six groups of proposed factors influenced the decision on local university choice in Vietnam in descending order of impact as follows: Study Costs, Majors, Influence Group, Quality and Reputation, Facilities, Advertising and Operations. The research model explains 62.4% for the overall relationship of the above 6 groups of factors with the dependent variable, which is Decision of choosing local university in Vietnam.